2012
DOI: 10.1093/jat/bks076
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Metformin Intoxication with Markedly Elevated Blood and Liver Concentrations

Abstract: The highest postmortem metformin concentrations are recorded utilizing a sensitive and specific analytical procedure. The peripheral blood metformin concentration was 240 mg/L, the liver concentration was 240 mg/kg and the gastric concentration was 1,700 mg. Additionally, an antemortem blood sample collected shortly after admission revealed a metformin concentration of 210 mg/L. These data, revealing a liver to peripheral blood ratio of 1.0, provide additional support that metformin is not subject to postmorte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…In Table 2, we have summarized the main clinical and postmortem findings (where available) in fatal cases related to therapeutic use or suicidal ingestion that we have collected upon literature review and the annual reports of the AAPCC from 2009 to 2011. Other fatal cases following therapeutic administration or suicidal use are mentioned in case series reports, but with limited available clinical and postmortem information [3,9,14,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Table 2, we have summarized the main clinical and postmortem findings (where available) in fatal cases related to therapeutic use or suicidal ingestion that we have collected upon literature review and the annual reports of the AAPCC from 2009 to 2011. Other fatal cases following therapeutic administration or suicidal use are mentioned in case series reports, but with limited available clinical and postmortem information [3,9,14,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the available data, metformin appears to be minimally susceptible to postmortem redistribution [17]. Blood levels ranging from 0.5 to 2.5 μg/ml are considered within the therapeutic range, whereas concentrations over 5 μg/ml are generally considered toxic [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. Lethal concentrations cannot be precisely defined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have shown that metformin does not accumulate in the plasma nor in any tissues other than the intestine, even with repeated administration (35). However, these results are from animal studies, and there are little data available on metformin levels in human organs (36).…”
Section: Discussionmentioning
confidence: 96%
“…Blood levels ranging from 0.5 to 2.5 μg/ml are considered within the therapeutic range, whereas concentrations over 5 μg/ml are generally considered toxic [15].…”
Section: Discussionmentioning
confidence: 99%